PERAN PENYULUH DALAM MENINGKATKAN PRODUKSI JAMBU METE DI KELURAHAN LAKUDO KECAMATAN LAKUDO KABUPATEN BUTON TENGAH - Ikbal Alimuddin; Iskandar Iskandar; La Ode Kasno Arif (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
The objective of this study is to ascertain the role of extension workers in enhancing cashew production and to identify the challenges they encounter in the implementation of agricultural extension in Lakudo Village, Lakudo District, Central Buton Regency. The study population consisted of all cashew farmers in Lakudo Village. The sample size was calculated using the Slovin formula with a 10% margin of error, resulting in a sample of 46 cashew farmers. The research sample was selected through the use of the simple random sampling method. This research employs a quantitative data approach. The data were collected via survey, interview, and documentation methods, with the media in the form of questionnaires or interviews. The variables of this study include the role of agricultural extension agents, constraints on agricultural extension agents, and increased cashew production. In the course of data processing, the data were subjected to interval classification analysis. The findings indicate that the role of agricultural extension officers in Lakudo Village, Lakudo District, Central Buton Regency has been effectively fulfilled, particularly in terms of their educational responsibilities. However, there is still room for improvement in the implementation of their role as leaders and advisors. In order to achieve increased cashew production, farmers must intensify their efforts or adopt more rigorous approaches to maintenance and harvesting. This will enable them to obtain more favourable production outcomes. Furthermore, post-harvest handling must be maintained and can be enhanced. There are no significant impediments to extension activities, in terms of distance, farmer participation, or facilities and infrastructure.